Current review of the literature: Stress reaction of the distal humerus - Moen, M.; Weir, A. (Medicine and Science in Tennis, 2007)
Stress reactions in the upper limb are relatively rare. Usually stress reactions are caused by traction of muscles on the periosteum or by maladaptation of the bone due to repetitive strain. They are common in the lower extremity, mainly in the distal tibia and in the second metatarsal. Maarten Moen and Adam Weir reviewed the following article: